Membrane distillation : surface modification, module modeling and system optimization - Zuo, Guangzhi (2014)
Compared to conventional separation processes, MD is potentially more cost-effective, especially when low-grade waste heat and/or alternative renewable energy sources being available for use. Though boasting a promising future for industrial application, several technical challenges still need to be tackled, including membrane wetting and fouling, relatively low membrane permeability (flux), concentration/temperature polarization effect, uncertainty of economic benefit, etc. Therefore, novel membrane development and improved module design will offer effective strategic solutions to these challenges. This thesis provides a comprehensive review of previous studies on MD with a focus on the areas of membrane wetting and fouling, especially when seawater is contaminated by spilled or discharged oil. Moreover, membrane module modeling based on computational fluid dynamics (CFD) and system optimization in terms of energy and economic analysis were also investigated. Overall, it is expected that the PhD study can help sought potential strategies to address the challenges for the practical application of MD process, such as the prevention of membrane wetting, reduction of membrane fouling by oil contamination, MD module modeling and system optimization, through better design and operation conditions.